Field evaluation of ethnomedicinal plants’ smoke knockdown and repellent efficacy against pre-bedtime biting malaria vectors in Mazowe district, Zimbabwe - David Singleton Nyasvisvo; Shadreck Sande; Rudo Sithole; Tamuka Nhiwatiwa (PLoS ONE, 2025)
The study investigated the knockdown and repellent efficacy of smoke from native plants, Vitex payos (Lour.) Merr., Peltophorum africanum Sond., and Adansonia digitata L., against malaria vectors in Bare ward, Mazowe district, Zimbabwe. Three to five-day-old An. gambiae sensu lato (s.l.) were exposed to smoke from the three plants over 150 minutes during knockdown tests. Mortality was scored after 24 hours. A randomized 4 x 4 Latin square design was used to assign plant smoke and control treatments to huts and nights during repellency tests. Repellency was estimated as percentage reduction in biting using CDC light traps between 1800 and 2200 hours. Burning charcoal without plant material was used as control. SPSS software was used for data analysis. KdT 50 and kdT 90 rates were determined using probit analysis. A negative binomial GLM with a log link function and an emmeans post-hoc test was used to model the number of An. funestus s.l. caught based on smoke treatment, night and hut. Vitex payos and P. africanum knocked down 100% of the An. gambiae s.l. within the 150-minute exposure period. The kdT 50 and kdT 90 rates were more rapid for V. payos (37.8 and 69.7 min) and P. africanum (44.8 and 89.7 min) than for A. digitata (77.8 and 146.9 min). The percent 24-hr mortality was 91.7 ( V. payos ) , 80 ( P. africanum ) and 71.6 ( A. digitata ) . Smoke from V. payos (86%, p = 0.008) and P. africanum (73%, p = 0.028) significantly reduced An. funestus s.l. biting. Smoke from V. payos and P. africanum merits further investigation since it has the potential to provide an additive benefit to ITNs by targeting proportions of malaria vectors that bite before bedtime. Studies to determine whether the use of smoke from these plants has a community effect that can lead to the reduction of malaria burden are required and significant.